PROFESSIONAL IDENTITY OF NURSING STUDENTS IN LITHUANIA AND POLAND - Skarbalius, Egidijus; Marcinowicz, Ludmila; Skarbalienė, Aelita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Nurses' professional identities develop throughout their lifetimes, from before entering nursing education, throughout their years of study and clinical experience, and continue to evolve during their careers. Education is, however, a key period as it is during this time students gain the knowledge and skills that separate nurses as healthcare professionals from people representing their professions. In order to purposefully shape the professional identity of nursing students, there is a need of knowing the level at which students identify themselves with the profession when graduating from a university. The aim of the study is to reveal the professional identity of nursing students in Lithuania and Poland and to make recommendations for improving the study process on the basis of the results of the study. A quantitative survey was conducted in the spring of 2017. The results of the research reveal that the professional identity of nursing students is rather of high level, the decision to work as nurses is strong, but there are some gaps in understanding of roles and responsibilities of nursing.